The Attitude of Birrul Waalidain Javanese Muslim Teenagers - Isnaya Arina Hidayati; Nurul Aisyah; Farha Isna Nur Abidah; Prima Afifah; Amalia Putri Hasna; Husain Ali As-Syafi’i (Universitas Muhammadiyah Surakarta, 2025)
Birrul waalidain is part of the ethics of a Muslim, especially for the younger generation of Muslims to be devoted to parents. In the concept of Islam, respecting parents is the key to one's success in the stages of life. In addition, in the context of Javanese culture which also upholds the value of respect for parents, the practice of Birrul waalidain in Muslim teenagers is an interesting encounter between religious teachings and local culture. This study aims to determine the current attitude of Birrul waalidain among Javanese Muslim teenagers. The approach used is descriptive qualitative, with six informants selected by purposive sampling with the criteria of adolescents aged 13-20 years, Muslim, and domiciled in Java. The data collection method was conducted through semi-structured interviews, and data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. As a result of this research, three themes emerged, namely Birrul waalidain's behavior, which was demonstrated by helping with housework, caring for, obeying, praying, making others proud, paying attention, and speaking softly. The next theme is Understanding the meaning of Birrul waalidain, which means making parents happy, obeying, helping, and praying. The final theme is the importance of Birrul waalidain, which is motivated by religious teachings, as an effort to repay kindness and maintain morals. These findings further implicate the importance of formal and informal early childhood Islamic Education to ensure a better social attitude in Javanese Muslim teenagers.